A Short Communication: Contamination and Toxicity Pigment Red 53, Rhodamine B, and Sudan III in Indonesian Cosmetics - Elanda Fikri; Yura Witsqa Firmansyah (Jurnal Serambi Engineering, 2023)
The high sales of cosmetic products in the world are not directly proportional to the good quality of cosmetic products. The The Food and Drug Administration (BPOM) declared, from October 2021 to August 2022 as many as 1 million pieces of cosmetic products contain Pigment Red 53, Rhodamine B, and Sudan III which are hazardous and prohibited ingredients. This study aims to disseminate information on case reports and toxicity of Pigment Red 53, Rhodamine B, and Sudan III contamination in Indonesian cosmetics. The study used a descriptive method with a case report study design. The study used secondary data, namely a list of cosmetic products containing Pigment Red 53, Rhodamine B, and Sudan III obtained from the website of the Indonesian authorities through the BPOM. Data collection was carried out on 4-5 October 2022. The BPOM declared 16 cosmetic products from 5 incorporated containing Pigment Red 53, Rhodamine B, and Sudan III. Undoubtedly, BPOM reported cases of Pigment Red 53, Rhodamin B, and Sudan III contamination still occurring from October 2021 to August 2022. The existence of these dyes should not be used as a mixture of cosmetics and personal care. In line with dangerous toxicity, these dyes are mutagenic, genotoxic, and carcinogenic. The BPOM must work even harder in its efforts to monitor safe cosmetic products to protect the health of the Indonesian people.